Shapes of openness : Bakhtin, Lawrence, laughter - Leone, Matthew (Cambridge Scholars Pub., 2010)
Uses Bakhtinian theory as a means of testing pertinent criticism of Lawrence, providing a conceptual basis for the readings of Lawrence's fiction, especially Women in love.